2018
DOI: 10.1371/journal.pone.0192145
|View full text |Cite
|
Sign up to set email alerts
|

KCa3.1 ion channel: A novel therapeutic target for corneal fibrosis

Abstract: Vision impairment from corneal fibrosis is a common consequence of irregular corneal wound healing after injury. Intermediate-conductance calmodulin/calcium-activated K+ channels 3.1 (KCa3.1) play an important role in cell cycle progression and cellular proliferation. Proliferation and differentiation of corneal fibroblasts to myofibroblasts can lead to corneal fibrosis after injury. KCa3.1 has been shown in many non-ocular tissues to promote fibrosis, but its role in corneal fibrosis is still unknown. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…The contribution of HDAC2 to tissue fibrosis is attracting increasing attention [ 48 , 49 ]. Recent studies showed that K Ca 3.1 inhibitors are a potential treatment option for renal, liver, kidney, corneal, and pulmonary fibrosis [ 50 , 51 , 52 , 53 , 54 ]. It currently remains unclear whether epigenetic modifications by HDAC2/3 are involved in these K Ca 3.1-related disorders; therefore, further studies are needed to clarify the therapeutic effectiveness of selective HDACis in various K Ca 3.1-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of HDAC2 to tissue fibrosis is attracting increasing attention [ 48 , 49 ]. Recent studies showed that K Ca 3.1 inhibitors are a potential treatment option for renal, liver, kidney, corneal, and pulmonary fibrosis [ 50 , 51 , 52 , 53 , 54 ]. It currently remains unclear whether epigenetic modifications by HDAC2/3 are involved in these K Ca 3.1-related disorders; therefore, further studies are needed to clarify the therapeutic effectiveness of selective HDACis in various K Ca 3.1-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that K Ca 3.1 blockade attenuated pulmonary, renal, and corneal fibrosis by mediating Smad2/3 signaling (Huang et al, 2013(Huang et al, , 2018Roach and Wulff, 2014;Roach et al, 2015;Anumanthan et al, 2018). The resultant decreases in Ca 21 influx prevented the phosphorylation of Smad2/3 and nuclear translocation of P-Smad2/3 in fibroblasts, and thus, the expression levels of the downstream target genes (a-smooth muscle actin and collagen type I) were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression has been reported in the development of fibrosis of the cornea and different organs (Huang et al, 2013;Roach et al, 2015). Treatment with the KCa3.1 inhibitor, TRAM-34, reduced the expression of pro-fibrotic markers, such as αSMA, in the corneal stroma (Anumanthan et al, 2018).…”
Section: Recombinant Proteins and Inhibitorsmentioning
confidence: 97%